The Farrakhan phenomenon : race, reaction, and the paranoid style in American politics - Singh, Robert (Georgetown University Press, 1997)
In this penetrating critical analysis of Louis Farrakhan's ascent to national influence, Robert Singh argues that the minister's rise to prominence is a function of race and reaction in contemporary America. Singh probes the origins and significance of Farrakhan in American politics. Drawing on published and unpublished records, personal interviews, and Farrakhan's writings and speeches, Singh places Farrakhan expressly within the "paranoid style" of such reactionaries as Jesse Helms and Joseph McCarthy. Examining Farrakhan's biographical details, religious beliefs, political strategies and relative influence, Singh argues that Farrakhan is an extreme conservative who exploits both black-white divisions and conflicts within the African-American community for personal advancement
Keywords: Farrakhan, Louis.; Farrakhan, Louis; United States -- Race relations.; African Americans -- Politics and government.; Hate -- Political aspects -- United States.; United States -- Politics and government -- 1989-; Noirs américains -- Politique et gouvernement.; Haine -- Aspect politique -- États-Unis.; États-Unis -- Relations raciales.; États-Unis -- Politique et gouvernement -- 1989-; SOCIAL SCIENCE -- Anthropology -- Cultural.; SOCIAL SCIENCE -- Discrimination & Race Relations.; SOCIAL SCIENCE -- Minority Studies.; African Americans -- Politics and government; Hate -- Political aspects; Politics and government; Race relations; United States; Rassenpolitik; Radikalismus; Populismus; Volksverhetzung; Rassenvraagstuk.; Black Muslims.; Since 1989; Hate -- Political aspects -- United States; United States -- Race relations